KAJIAN ANTROPOLOGI SASTRA DALAM NOVEL TENGGELAMNYA KAPAL VAN DER WIJCK KARYA HAMKA - Aura Shafa Apriliana; Eka Fitriyani; Ahmad Supena (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2026)
This study aims to describe the study of literary anthropology contained in the novel Tenggelamnya Kapal Van der Wijck by Hamka, with an emphasis on two main aspects: (1) the value of the relationship between humans and God, and (2) the value of the relationship between individuals. The study of literary anthropology examines the relationship of influence between literary works and the underlying culture. This study applies a qualitative approach with the hermeneutic method, and utilizes data obtained comprehensively from the contents of the novel Tenggelamnya Kapal Van der Wijck.